The role of nitrogen in transforming British agricultural productivity production prior to and during the First World War. (1st October 2020) - Martin, John
This paper explores the reasons why artificial or mineral sources of nitrogen, which were more readily available in Britain than in other European countries, were only slowly adopted by farmers in the decades prior to and during the First World War. It considers why nitrogen in the form of sulphate of ammonia, a by-product of coal-gas (town-gas) manufacture, was increasingly exported from Britain for use by German farmers. At the same time Britain was attempting to monopolise foreign supplies of Chilean nitrate, which was not only a valuable source of fertiliser for agriculture but also an essential ingredient of munitions production. The article also investigates the reasons why sulphate of ammonia was not more widely used to raise agricultural production during the First World War, at a time when food shortages posed a major threat to public morale and commitment to the war effort.